The Items Development of Social Skills for Autism Spectrum Disorder (SS-ASD) Instrument (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Currently, there is a need to develop a reliable and valid social skills observation instrument in monitoring the progress of social skills among students with ASD in teaching and learning within school setting. This is because positive and acceptable social skills are very important aspects for students with ASD. Moreover, students with ASD who hold a strong foundation in social skills shown an improvement in academic, independent living and social acceptance by the society. The instrument was based on structured observations and there were three steps involved: (a) instrument selection, (b) item selection, and (c) validity and reliability instrument. These steps were to ensure the development of instrument was appropriate to specifically measure the progress of social skills within specific domain namely: social interaction, social communication, emotional intelligence and social behavior. The instrument was namely as “Social Skills for Autism Spectrum Disorder (SS-ASD)”. Accordingly, the SS-ASD was given to 2 subject experts and 1 curriculum specialist to establish content validity and face validity. Hence, the SS-ASD instrument had established construct validity through homogeneity (internal consistency) by calculating the value of Cronbach’s alpha (α) through pilot study data.  Finally, the Cronbach’s Alpha value for SS-ASD was 0.986 and it was highly reliable. The SS-ASD were developed suitable for children between ages 3 to 12 years old as a criterion-based instrument. Hopefully, its help students with ASD establish proficiency in social skills that create social acceptance and independent living in the future for students with ASD.